2016
DOI: 10.1371/journal.pone.0153033
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Pump Therapy Is Associated with Lower Rates of Retinopathy and Peripheral Nerve Abnormality

Abstract: ObjectiveTo compare rates of microvascular complications in adolescents with type 1 diabetes treated with continuous subcutaneous insulin infusion (CSII) versus multiple daily injections (MDI).Research Design and MethodsProspective cohort of 989 patients (aged 12–20 years; diabetes duration >5 years) treated with CSII or MDI for >12 months. Microvascular complications were assessed from 2000–14: early retinopathy (seven-field fundal photography), peripheral nerve function (thermal and vibration threshold testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 25 publications
2
49
2
3
Order By: Relevance
“…Yet, the RCT studies that have not shown a lowering of HbA1c have highlighted the endorsement of pump therapy as patients randomized to the technology continued its use by the end of the study, had higher reports of treatment satisfaction, and reported decreased diabetes‐related worry . Interestingly, prospective examination of nearly 1000 patients either on pump or MDI therapy found that despite similar HbA1c levels attained, lower rates of retinopathy and peripheral nerve abnormality were noted in the insulin pump treated group . Furthermore, data from meta‐analyses conducted by various groups have depicted similar findings with pump therapy.…”
Section: Insulin Pumpsmentioning
confidence: 99%
“…Yet, the RCT studies that have not shown a lowering of HbA1c have highlighted the endorsement of pump therapy as patients randomized to the technology continued its use by the end of the study, had higher reports of treatment satisfaction, and reported decreased diabetes‐related worry . Interestingly, prospective examination of nearly 1000 patients either on pump or MDI therapy found that despite similar HbA1c levels attained, lower rates of retinopathy and peripheral nerve abnormality were noted in the insulin pump treated group . Furthermore, data from meta‐analyses conducted by various groups have depicted similar findings with pump therapy.…”
Section: Insulin Pumpsmentioning
confidence: 99%
“…CSII allows the administration of lower doses of insulin, lowering of the HbA1c without inducing a higher risk of hypoglycemia, and greater flexibility in eating habits and physical activity . Moreover, it was shown that CSII therapy reduces chronic diabetes complications in comparison with MDI, despite them having similar HbA1c . Despite the confirmed effects of insulin pump therapy, this technology is still not available in two European countries, and significant burdens in CSII accessibility were reported for seven others.…”
Section: Discussionmentioning
confidence: 99%
“…Children on insulin pumps present lower glycaemic variability and a lower glycaemic profile compared with those using MDI . Treatment with CSII is also associated with lower rates of retinopathy and peripheral nerve abnormality in adolescents . Further, this kind of therapy is associated with a considerable reduction in the risk of fatal coronary heart disease, fatal cardiovascular disease, and all causes of mortality .…”
Section: Introductionmentioning
confidence: 99%
“…9 Treatment with CSII is also associated with lower rates of retinopathy and peripheral nerve abnormality in adolescents. 10 Further, this kind of therapy is associated with a considerable reduction in the risk of fatal coronary heart disease, fatal cardiovascular disease, and all causes of mortality. 11 Additionally, use of CSII from the onset of diabetes improves treatment satisfaction.…”
mentioning
confidence: 99%